Experimental and Numerical Analysis of Structural Capacity of Perforated Stiffened Plates - S. Saad-Eldeen; Yordan Garbatov (Journal of Marine Science and Engineering, 2023)
This study presents experimental and numerical analyses of compressive collapse tests of initially corroded steel-stiffened plates with multiple circular openings, which may be used as tank wash plates. The ultimate load-carrying capacity and the relevant collapse modes are identified. The load-axial/lateral displacement relationships and local strain for each opening degree are analysed with developed regression equations for the ultimate capacity of stiffened plates as a function of different degrees of openings and the resting volume and residual cross-sectional area. A series of finite element analyses are performed. The experimental and numerical results are compared and show the complexity of predicting the ultimate capacity and the collapse mode as the degree of openings increases. The experimental results are compared for aged steel plates, and high-tensile stiffened plates considering the same degrees of openings, showing good agreement.